Difference in rugby league match characteristics following the introduction of temporary law modifications due to COVID-19: A preliminary investigation - Rennie, G.; Dalton-Barron, N.; Weaving, D.; Jones, B. (Sport Performance & Science Reports, 2020)
Super League (SL) is the highest level of rugby league competition in the Northern Hemisphere. The league competition was postponed on 24th Match 2020, due to the global COVID-19 pandemic, and restarted on the 2nd August 2020. With the aim of reducing the number of close proximity encounters within matches, a number of risk mitigation factors were implemented by the Rugby Football League (RFL). These included the temporary removal of the scrum and the addition of the `6 again` rule. These changes will likely have an effect on the match characteristics (e.g., locomotor variables and match events) albeit this is not causal (1). Whilst the locomotor (2,3), collision (4,5) and match event characteristics (6,7) have been previously described, these were when rugby league was played with scrums.